2016 IEEE 24th International Requirements Engineering Conference (RE) 2016
DOI: 10.1109/re.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on Handling Requirements and Acceptance Test Documentation in Industry

Abstract: With the emergence and spread of agile processes, the practices of writing and maintaining documentation have drastically changed in the last decade. In this work, we performed a qualitative study to explore the current practices for managing two related types of software documentation: requirements and acceptance tests. We interviewed twenty practitioners from seventeen business units in fifteen companies to investigate the companies' practices for writing, maintaining and linking requirements and acceptance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
13
0
3
Order By: Relevance
“…Having non-aligned documents increases the risk of the late discovery of a mismatch between stakeholders' expectation and the actual software behaviour, which is one of the main reasons for the failure of many software projects [14]. In an earlier study, we found that requirements and acceptance tests are not aligned mostly due to (1) the manual effort needed for keeping the documents in a consistent state, (2) preferable verbal communication between requirements and test engineers and (3) the separation of the requirements and testing activities [9].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Having non-aligned documents increases the risk of the late discovery of a mismatch between stakeholders' expectation and the actual software behaviour, which is one of the main reasons for the failure of many software projects [14]. In an earlier study, we found that requirements and acceptance tests are not aligned mostly due to (1) the manual effort needed for keeping the documents in a consistent state, (2) preferable verbal communication between requirements and test engineers and (3) the separation of the requirements and testing activities [9].…”
Section: Introductionmentioning
confidence: 93%
“…3) Notifying subscribed parties: We found in our previous study that testers are often not informed about changes in requirements [9]. Therefore, when a test fails, testers need a significant amount of time to realize that the cause is not a bug in the source code, but a change in the requirements.…”
Section: Approach Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, however, impacted artifacts too often are not kept aligned with changing requirements. To a significant extent, this is due to the additional effort required and to insufficient communication of requirement changes [1,2]. Losing the alignment between requirements and other documentation artifacts increases the risk of discovering mismatches between stakeholders' expectations and the actual software behavior only late, leading to unintended costs, delivery delays and unsatisfied customers.…”
Section: Introductionmentioning
confidence: 99%